A Charlie Brown Thanksgiving [videorecording (Blu-Ray)] - Guaraldi, Vince
When Peppermint Patty and friends show up at Charlie Brown's on Thanksgiving unexpectedly, Chuck, with the help of Linus, Snoopy, and Woodstock, shows them the true meaning of Thanksgiving.